Living Hadis : Studi atas Tradisi Sedekah Nasi Bungkus Hari Jumat oleh Komunitas Sijum Amuntai - Muhammad Rafi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Poverty is one of the most complex and very significant social problems in influencing social-community settings. Islam through the Qur'an and Sunnah has provided a solution to overcome this poverty problem with the concept of alms. Alms itself is not limited to only assets or material, but can also be done through physical effort, one of which is good deeds to others. There are many verses of the Qur'an and matan hadith that invite Muslims to give alms, either openly or secretly. Then, the text is understood and actualized by Muslims with various kinds of understanding and forms of implementation. This is what later referred to as the hadith living. Living hadith is a sunnah of the Prophet which is freely interpreted by ulama, rulers, judges and Muslims according to the situation, place and conditions they face, or also referred to as